Open Reduction and Internal Fixation of Pediatric Scapula Fractures: A Report of 2 Cases. Issue 1 (10th January 2022) - Schultz, Blake J.; Davis, Elizabeth P.; Chang, Gerard; Ward, Norman H.; Berkes, Marschall; Choo, Andrew M.
Abstract : Case: Two pediatric patients with displaced, extra-articular scapula fractures who underwent surgery because of concerns for persistent deformity and decreased function with continued nonoperative management. Conclusion: We advocate careful consideration of all patient factors and treatment options when addressing pediatric scapula fractures. Specific fracture patterns with altered shoulder girdle mechanics may warrant surgical intervention to restore anatomic alignment and stability.